A review of Medical Diagnostics Via Data Mining Techniques - Rasheed, Sarah Sameer; faisal, suhad; Kamil Mohammed, Iyden; S. Abd, Mustafa (Iraqi Journal of Science, 2021)
Data mining is one of the most popular analysis methods in medical research. It involves finding patterns and correlations in previously unknown datasets. Data mining encompasses various areas of biomedical research, including data collection, clinical decision support, illness or safety monitoring, public health, and inquiry research. Health analytics frequently uses computational methods for data mining, such as clustering, classification, and regression. Studies of large numbers of diverse heterogeneous documents, including biological and electronic information, provided extensive material to medical and health studies.